KREATIVITAS DAN INOVASI PENGARUHNYA TERHADAP PEMASARAN KEWIRAUSAHAAN PADA USAHA KECIL - Ernani Hadiyati (Asian Journal of Innovation and Entrepreneurship, 2012)
Creativity and innovation is a topic that is relevant not only for the entrepreneurs who are just starting, but also for business activities in general. The concept of entrepreneurial marketing is a scientific discipline that studies about the value, capabilities and a person's behavior in dealing with various issues related to business opportunities in an effort to get done. The purpose of this study are: first, to determine and analyze creativity and innovation have a significant effect simultaneously on entrepreneurial marketing. Second, to identify and analyze creativity and innovation have a significant effect partially towards entrepreneurial marketing. Third, to identify and analyze between creativity and innovation are the dominant influence on entrepreneurial marketing. The research location is determined at small business centers Ceramic Dinoyo Malang. The number of small businesses as respondents: 34 business units. Data analysis tool used is multiple linear regression using the F test and T test. Based on the results of data analysis using multiple linear regression, the results of the study are as follows: First, creativity and innovation have a significant effect simultaneously on entrepreneurial marketing. Second, creativity and innovation have a significant effect partially towards entrepreneurial marketing. Third, creativity is the dominant influence on entrepreneurial marketing. Keywords: Creativity, innovation entrepreneurial marketing